1995
DOI: 10.1172/jci117762
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure regulates platelet-derived growth factor A-chain gene expression in vascular smooth muscle cells in vivo. An autocrine mechanism promoting hypertensive vascular hypertrophy.

Abstract: To clarify the role of PDGF A-chain in hypertensive vascular hypertrophy of spontaneously hypertensive rats (SHRs), we studied levels of PDGF A-chain gene expression and transcription factors related to the gene in vascular smooth muscle cells (VSMCs) of SHRs in vivo. RNase protection assay and in situ hybridization showed that PDGF A-chain mRNA levels in VSMCs of SHRs were twofold higher than in those of normotensive Wistar-Kyoto rats. Gel retardation assays showed that levels of Spl and AP-2 in VSMCs of SHRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Previous work from this laboratory showed that PDGF-A expression and vascular wall hypertrophy both correlate with blood pressure in the 1K1C hypertensive rat (6). Decreasing blood pressure by different antihypertensive agents in the SHR also produced a decrease in PDGF-A expression and aortic hypertrophy, both of which correlated with the change in blood pressure (29). These results from two different models of hypertension suggest that pressure mediates PDGF-A expression in the arterial VSMCs.…”
Section: Discussionmentioning
confidence: 52%
“…Previous work from this laboratory showed that PDGF-A expression and vascular wall hypertrophy both correlate with blood pressure in the 1K1C hypertensive rat (6). Decreasing blood pressure by different antihypertensive agents in the SHR also produced a decrease in PDGF-A expression and aortic hypertrophy, both of which correlated with the change in blood pressure (29). These results from two different models of hypertension suggest that pressure mediates PDGF-A expression in the arterial VSMCs.…”
Section: Discussionmentioning
confidence: 52%
“…The transcription factor Sp1 positively regulates target gene expression upon BP rise in vascular smooth muscle cells. 32 After the demethylation of H3K27me3, Sp1 that is recruited to the promoter may lead to positive regulation of the Nkcc1 gene with co-activators such as histone acetyltransferases in hypertensive rats. Although Ang II increased the histone acetylation for IGF-IIreceptor gene expression, 33 it is still not clear whether the upregulation of the Nkcc1 gene promoter activity is caused by indirect mechanisms downstream of Ang II, such as oxidative stress and high BP, or by a direct mechanism through the activation of Ang II receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasized the role that PDGF-A may play in the remodeling of the arterial wall in hypertension. Increased PDGF-A expression has been found in aortas of spontaneously hypertensive rats (SHR) and angiotensin-treated rats (26,42). Moreover, the treatment of SHR with antisense oligonucleotides for PDGF-A significantly reduced hypertrophy of the thoracic aorta, without altering blood pressure (11).…”
Section: Discussionmentioning
confidence: 99%
“…Also, smooth muscle cells isolated from thoracic aortas of newborn and adult rats constitutively express PDGF-A message (33,36). There are data showing enhanced expression of PDGF-A chain mRNA in thoracic aorta of spontaneously hypertensive rats (26), hypertensive Sprague-Dawley rats (23), and angiotensin-treated Wistar rats (42).…”
mentioning
confidence: 99%